1994
DOI: 10.1007/bf01923453
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aspects of the hsp70 multigene family in vertebrates

Abstract: The family of genes encoding heat shock proteins of about 70 kDa (hsp70) in vertebrates is reviewed under genetic aspects. After a detailed description of the various hsp70 genes more general characteristics of the organization and evolution of the multigene family are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
9

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 81 publications
(3 reference statements)
4
69
0
9
Order By: Relevance
“…In CD8 cells (aside from the canonical example of CD8␣͞CD8␤), the most differentially expressed gene was CCR9, a receptor for the TECK ligand on thymic dendritic cells and intestinal enterocytes. Expression of CCR9 by DP thymocytes is down-regulated on CD4 thymocytes and may distinguish recent thymic emigrants in peripheral lymphoid tissues and intestinal lamina propria (29)(30)(31) (32). Although the role of HSP70.1 in thymic development has not been established, generalized overexpression of an HSP 70.1 transgene results in selective developmental arrest of thymocyte differentiation at the DP stage (33).…”
Section: Resultsmentioning
confidence: 99%
“…In CD8 cells (aside from the canonical example of CD8␣͞CD8␤), the most differentially expressed gene was CCR9, a receptor for the TECK ligand on thymic dendritic cells and intestinal enterocytes. Expression of CCR9 by DP thymocytes is down-regulated on CD4 thymocytes and may distinguish recent thymic emigrants in peripheral lymphoid tissues and intestinal lamina propria (29)(30)(31) (32). Although the role of HSP70.1 in thymic development has not been established, generalized overexpression of an HSP 70.1 transgene results in selective developmental arrest of thymocyte differentiation at the DP stage (33).…”
Section: Resultsmentioning
confidence: 99%
“…Previous data indicated that the Hsp70 chaperone family lacks a conventional signal peptide sequence that would allow them to be transported through cytosolic or plasma membranes [35]. Consequently, transport [37,40] would require either increased cell membrane permeability [29] or a specific exocytotic pathway, as already was reported from a hepatosplanchnic source [28] and from the brain [45] following body exercise.…”
Section: The Origin Of Salivary Chaperone Hsp70mentioning
confidence: 93%
“…The mouse and human Hsp70 genes located in the MHC locus are expressed by transcription factors other than HSF1 (Morimoto et al 1990;Wu 1995). Conversely, given that the zebrafish hsp70 shows strict heat-inducible expression, it appears to undergo a simple transcriptional regulation that may involve only HSF, a system that is similar to that observed for the Drosophila and human HSP70B′ (Craig et al 1979;Voellmy et al 1985;Morimoto et al 1990;Gunther and Walter 1994).…”
Section: -1 Stress Responses In Embryosmentioning
confidence: 94%
“…3) . On the other hand, two distinct mammalian groups have been identified, namely, a Major Histocompatibility Complex (MHC)-linked group consisting of human HSP70- 1 and HSP70-2 and mouse HSP70.1 Wu et al 1985;Milner and Campbell 1990) and a group containing the human and pig HSP70B′ (Voellmy et al 1985;Gunther and Walter 1994). Thus, the heat-inducible HSP70s may have diverged into several distinct groups during vertebrate evolution.…”
Section: -2 Zebrafish Hsp70mentioning
confidence: 99%